2018
DOI: 10.1155/2018/1376231
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for the Determination of Benzocaine and Procaine in Pharmaceuticals by Single-Sweep Polarography

Abstract: A new polarographic method for the determination of benzocaine and procaine based on the polarographic reduction of their chemically obtained oxidation products with potassium peroxymonosulfate is developed. Experimental conditions affecting quantitative yield of benzocaine and procaine oxidation products such as рH, oxidation time, reagents’ concentration, and temperature are explored. It is shown that the reduction current changes in a linear fashion (R=0.999) with increasing concentration of anesthetics ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The proposed method demonstrated to be very sensitive, as indicated by the low values (below 1 mg L −1 ) of the LOQ obtained. These LOQs were lower or comparable to those reported in previous works using CE [33,36,37,43], HPLC [12][13][14][15][16][17][18][19][20][21][22], and electrochemical detection [23,[25][26][27]. The intra-day precision was assessed by analyzing in triplicate (in the same day) six different samples of pharmaceutical formulations (three samples containing LD and other three with BZ).…”
Section: Validation Of the Ce-uv Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The proposed method demonstrated to be very sensitive, as indicated by the low values (below 1 mg L −1 ) of the LOQ obtained. These LOQs were lower or comparable to those reported in previous works using CE [33,36,37,43], HPLC [12][13][14][15][16][17][18][19][20][21][22], and electrochemical detection [23,[25][26][27]. The intra-day precision was assessed by analyzing in triplicate (in the same day) six different samples of pharmaceutical formulations (three samples containing LD and other three with BZ).…”
Section: Validation Of the Ce-uv Methodssupporting
confidence: 73%
“…In addition to HPLC methods of analysis for determination of LD and BZ in pharmaceutical formulations [12][13][14][15][16][17][18][19][20][21][22], analytical methods based on electrochemical [23][24][25][26][27] and spectrophotometric [28][29][30][31] detections have also been reported in the literature. Beyond quantification of LD in pharmaceutical formulations [32][33][34][35], CE has also been applied for the determination of this anesthetic in urine [36][37][38], human plasma [39,40], human serum [41,42], vitreous humor [43], and seized cocaine [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In general, a local anesthetic with a relatively high concentration is needed to be topically effective, amplifying the toxicity risk and tissue penetration. 1,2 Along with the needed effects of BZC, it can induce numerous adverse effects such as urticaria and dermatitis, stinging and burning, methemoglobinemia and angioedema. 3 Various experiments showed that excessive doses of anaesthetic sprays containing BZC would cause life-threatening and cyanosis complications.…”
Section: Introductionmentioning
confidence: 99%
“…PRO was prepared in 1905 for the first time afterward, amylocaine. PRO is used for spinal anesthesia, therapeutic, and local infiltration blockade [2].…”
Section: ■ Introductionmentioning
confidence: 99%